Molecular manipulations of miR398 increase rice grain yield under different conditions - Lu, Yuzhu; Yao, Kena; Gong, Zhiyun; Zhang, Yixin; Meng, Yunlong; Liu, Qiaoquan (Frontiers in Plant Science, 2022)
Rice miR398 targets two stress-tolerant genes, CSD1-2 (Cu/Zn Superoxide Dismutases1-2) and CCS (copper chaperone of CSD), which usually boost plants’ tolerance by inhibiting growth. So, how to accurately regulate the activities of miR398 targets and thus make rice better able to adapt to different conditions has great significances in producing rice yields under the current circumstances of shrinking arable lands resulting from global urbanization and increasing salty soil caused by irrigation. Through controlling the expressions of miR398 in different levels, we found down-regulated expression of miR398 targets can promote growth under good growth conditions while up-regulated expressions of the targets can help rice tolerate salt. In this study, we over-expressed miR398 highly, moderately, and lowly, then three concomitantly inverse levels of its targets’ expression were obtained. Under normal growth conditions, the transgenic lines with low and moderate levels of over-expressions of miR398 could increase grain yields 14.5% and 7.3%, respectively, although no transgenic lines could survive well under salty conditions simulating real saline-alkali soil. Using short tandem target mimic (STTM) technology to silence miR398 highly, moderately, and lowly respectively, also three inverse levels of its targets’ expression were obtained. All three transgenic lines exhibited good agronomic performances under salt stress in inverse to their degrees of STTM, but their growth was inhibited differently under normal conditions. Altogether, we suggest that flexibly manipulating the expression of miR398 is an ideal strategy to help rice survive better and achieve optimized yields under specific conditions.